Certificateless Signature Scheme Based on Rabin Algorithm and Discrete Logarithm - Xiangjun Xin; Chaoyang Li (Universitas Ahmad Dahlan, 2016)
Certificateless signature can effectively immue the key escrow problem in the identity-based signature scheme. But the security of the most certificateless signatures usually depends on only one mathematical hard problem, which makes the signature vulnerable when the underlying hard problem has been broken. In order to strengthen the security, in this paper, a certificateless signature whose security depends on two mathematical hard problems, discrete logarithm and factoring problems, is proposed. Then, the proposed certificateless signature can be proved secure in the random oracle, and only both of the two mathematical hard problems are solved, can the proposed signature be broken. As a consequence, the proposed certificateless signature is more secure than the previous signatures. On the other hand, with the pre-computation of the exponential modular computation, it will save more time in the signature signing phase. And compared with the other schemes of this kind, the proposed scheme is more efficient.